Nanotechnology-Based Strategy to Upgrade the Performances of Plastic Flexible Film Waste - Garofalo, Emilia (Polymers (Basel), 2019)
The aim of this work was to improve the performances of Fil-s (film-small), a recycled material obtained from plastic flexible film waste that is made of polyethylene and a minor amount of polypropylene, with traces of polar contaminants (polyamides, maleic anhydride, etc.). The idea was to upgrade the material’s mechanical properties by applying a nanotechnology-based strategy that takes advantage of the composition of Fil-s. In particular, different amounts of copolyamide (CoPA) and its masterbatch with an organic-modified nanosilicate were melt compounded with Fil-s in a twin-screw extruder. The good affinity between Fil-s and CoPA, proved by means of spectroscopic and rheological analysis, allowed for the obtaining of a well-refined morphology for the neat and hybrid blends. This resulted in very interesting increments of the strain at break, which was particularly impressive (10 times higher) in the case of the blend with the lower amount of copolyamide masterbatch, but without sacrificing the stiffness and strength of Fil-s.